Improvement of the efficiency of vertical-axis wind turbines using a wind flow concentrator - Kolisnyk, O.; Gorobets, V. (Energy and Automation, 2026)
The relevance of the study is driven by the necessity to enhance energy efficiency and improve the start-up characteristics of autonomous power generation systems, particularly vertical-axis wind turbines, in low-potential wind flow conditions (3–5 m/s) typical for most regions of Ukraine. The purpose and objectives of the research consist in the development and investigation of a stationary aerodynamic wind flow concentrator of the confuser type to lower the self-starting threshold and increase the output power of the wind generator. The research methods are based on experimental modeling of a modified electromechanical system (Savonius rotor with a PMG-20 generator) in a subsonic wind tunnel under an active electrical load of 230 Ω. The research results demonstrated that the application of guide vanes enables the implementation of the Venturi effect, providing local air acceleration on the working blades and shielding of the blades moving against the wind. A 30% reduction in the self-starting speed threshold (from 2.7 m/s to 1.9 m/s) was experimentally confirmed. It was established that at a wind speed of 4.0 m/s, the output electrical power increases by 3.6 times compared to the baseline rotor configuration. Conclusions: the application of the developed aerodynamic concentrator design is an effective scientific and technical solution for expanding the operating range and improving the generation stability of low-power vertical-axis wind turbines.Recieved: 28.01.2026.  Recieved: 21.03.2026. Accepted: 17.04.2026.
Keywords: wind power plant; vertical axis; aerodynamic concentrator; self-starting; energy efficiency; active load